Pemberdayaan Masyarakat Desa untuk Pencegahan dan Penanganan Kasus Kekerasan dalam Rumah Tangga Desa Pematang Serai - Muhammad Harry Angga Pratama Sinaga; Muhammad Chaerul Rizky; Fitri Rafianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The aim of this outreach activity is to increase knowledge, understanding and strengthening of the Pematang Serai Village Community regarding the prevention of domestic violence and divorce. The importance of conveying this material is because cases of divorce and domestic violence are increasing, especially during the COVID-19 pandemic. During this pandemic, women's vulnerability to violence, especially domestic violence, has increased, as can be seen from the increase in reports of violence against women in several regions in Indonesia, including North Sumatra Province. There are various factors that have caused an increase in domestic violence during the COVID-19 pandemic, including social and economic factors. In this community service activity, we use lecture, discussion and consultation methods to increase the knowledge and understanding of the target audience. The results of this outreach activity show an increase in the knowledge of the Pematang Serai Village community about preventing domestic violence and divorce after an evaluation was carried out.